Iowa Birdline update, February 18, 1991 notes - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Notes for the Iowa Birdline update for February 18, 1991. Highlights include large numbers of diving ducks and gulls along the Mississippi River as far north as Le Claire. Epson - sheet feed/flatbed